اردو سیرت نگاری ۲۰۱۸؍ میں(تعارفی اورتجزیاتی مطالعہ): Urdu Biography in 2018 (Introductory and Analytical Study) - Syed Aziz Ul- Rehman, (Seerat Studies, 2023)
Maalan Dabaamil hal Tschach ek Diman Enbadi Watr Rip Dahthi and Al-Bairiyy Issanee. Atkb and in the morning atkb They have a relationship with each other, and today and forever. You are the person of the prince and the mother is here It is a source of fear and fear for the hook of the day and the Urdu and the Coptic. This Zari Rizn Atakb, you are the one who is the one of the people of Malat and the people of Malat. Aagaz Basah Narrative Arqaa is a source of the first and last, and the second is the first and last. The reward of the students is one and the same.